2016
DOI: 10.1091/mbc.e14-04-0935
|View full text |Cite
|
Sign up to set email alerts
|

From CFTR biology toward combinatorial pharmacotherapy: expanded classification of cystic fibrosis mutations

Abstract: More than 2000 mutations in the cystic fibrosis transmembrane conductance regulator (CFTR) have been described that confer a range of molecular cell biological and functional phenotypes. Most of these mutations lead to compromised anion conductance at the apical plasma membrane of secretory epithelia and cause cystic fibrosis (CF) with variable disease severity. Based on the molecular phenotypic complexity of CFTR mutants and their susceptibility to pharmacotherapy, it has been recognized that mutations may im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
436
1
12

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 491 publications
(480 citation statements)
references
References 92 publications
5
436
1
12
Order By: Relevance
“…Several lines of evidence suggest multiple defects in W1282X-CFTR and support corrector, potentiator, and readthough strategies (12). Transcript encoding W1282X-CFTR was seen in nasal epithelial cells of homozygous W1282X CF subjects with 30 -80% abundance compared with that of wild type CFTR in non-CF subjects (13).…”
mentioning
confidence: 99%
“…Several lines of evidence suggest multiple defects in W1282X-CFTR and support corrector, potentiator, and readthough strategies (12). Transcript encoding W1282X-CFTR was seen in nasal epithelial cells of homozygous W1282X CF subjects with 30 -80% abundance compared with that of wild type CFTR in non-CF subjects (13).…”
mentioning
confidence: 99%
“…CFTR mutations are classified according to their disruptive mechanisms, and therapies targeting the underlying cause are directed by mutation class (2,3). The class III G551D CFTR mutation results in a properly localized but dysfunctional channel.…”
mentioning
confidence: 99%
“…The mutation also reduced the channel's opening rate, indicating that one mutation could have multiple deleterious consequences. Indeed, later studies showed that the Phe508del mutation also reduced Phe508del lifetime at the cell membrane (37)(38)(39).…”
Section: Understanding How Mutations Cause Dysfunction Of the Gene Prmentioning
confidence: 99%
“…Other genetic variations (modifier genes), epigenetic modifications, and environmental exposures, including viral infections, can also determine the consequences of CFTR mutations in individuals. The availability of small molecules targeting CFTR is also providing an opportunity to identify mutations that respond to distinct chemicals (39,40).…”
Section: Understanding How Mutations Cause Dysfunction Of the Gene Prmentioning
confidence: 99%